A Functional Model for the Rieske Center: Full Characterization of a Biomimetic N‐Ligated [2Fe‐2S] Cluster in Different Protonation States. Issue 31 (18th June 2013) - Albers, Antonia; Bayer, Thomas; Demeshko, Serhiy; Dechert, Sebastian; Meyer, Franc
<x xml:space="preserve">Abstract</x> Give and take both: A bis(benzimidazolate)‐capped biomimetic [2Fe‐2S] cluster has been characterized in different protonation states, both in the diferric and mixed‐valent forms. Protonation does not lead to structural changes of the [2Fe‐2S] core, but facilitates its reduction and causes pronounced valence localization in the mixed‐valent state. Concerted proton and electron transfer back to the diferric cluster emulates a key step in the function of mitochondrial Rieske proteins (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>